Mixed Phenotype Acute Leukemia, B/Myeloid (Bilineal and Biphenotypic), With t(2;22)(q35;q12);EWSR1-FEV. Issue 3 (April 2021) - Montgomery-Goecker, Crystal; Koduru, Prasad; Botten, Giovanni; Xu, Jian; Ghisoli, Maurizio; Goldman, Stanton C.; Krueger, JoEllen; Bhushan, Vikas; Fuda, Franklin; Chen, Weina
Abstract : Background: Ewing sarcoma breakpoint region 1 gene ( EWSR1 ) rearrangements are largely associated with the Ewing sarcoma family of tumors. Observations: We report the first case of infantile, mixed phenotype acute leukemia, B/myeloid (bilineal and biphenotypic [B-lymphoid and B-lymphoid/myeloid]), with a t(2;22)(q35;q12). The EWSR1 -fifth Ewing variant gene fusion and nonsense mutation in STAG2 were detected by next-generation sequencing and markedly high expression of fifth Ewing sarcoma variant mRNA detected by quantitative reverse transcription polymerase chain reaction. The patient was treated with a combined myeloid/lymphoid leukemia regimen followed by allogeneic stem cell transplant and was in complete remission at 3.8-year follow-up. Conclusions: Our case study underscores the importance of a comprehensive evaluation of acute leukemia and provides insights into the phenotype of EWSR1 rearranged neoplasms in the context of partner genes and cell type.